IDENTIFYING THE ETHICAL ISSUES IN TWITTER: A KNOWLEDGE ACQUISITION FOR ONTOLOGY - Mohamed Najid, Mohamad Hafizuddin; Zulkifli, Zahidah; Othman, Roslina; Rokis, Rohaiza; Salahuddin, Ashraf Ali (Malaysian Journal of Computer Science, 2021)
Social media is an open platform to communicate, share and exchange information freely. This uncontrolled exchanged information carries out both negative and positive impacts in others’ lives. In this regard, this study aims to identify ethical issues on this information in line with Ibn Khaldun’s ethical considerations. Out of many other social networking sites, Twitter has been identified as one of the most popular microblogging social networking platforms. Using a simple algorithm in R programming and 43 keywords based on Ibn Khaldun’s thoughts, 1075 public tweets have been extracted from Twitter as a sample of ethical issues. The sentiment analysis in Parallel Dots was performed on the collected tweets, and it was discovered that 700 of the tweets are positive statements, 229 are neutral statements, and 146 are negative statements. Having done the validation process on these sentiments, the study proposed these identified ethical issues from tweets as a domain in developing ontology relationships with Ibn Khaldun’s thoughts. In this process, further study can be carried on with wider data from various sources beyond the limitation of this study. Thus, a semantic database could serve as a guideline for SNS ethical issues based on Ibn Khaldun’s thoughts.